Validation of Computationally Efficient Simulations of Douglas Fir Pyrolysis and Combustion Using Time-Resolved Frequency Comb Laser Measurements - Glusman, Jeffrey F.; Lapointe, Caelan B.; Makowiecki, Amanda S.; Simons-Wellin, Sam; Rieker, Gregory B.; Daily, John W.; Hamlington, Peter E. (Frontiers in Forests and Global Change, 2022)
Computational simulations have the potential to provide low-cost, low-risk insights into wildland fire structure and dynamics. Simulation accuracy is limited, however, by the difficulty of modeling physical processes that span a wide range of spatial scales. These processes include heat transfer via radiation and turbulent advection, as well as both solid- and gas-phase chemistry. In the present study, we perform large eddy simulation (LES) with adaptive mesh refinement to model the multi-phase pyrolysis and combustion of dry Douglas fir, where temperature-based lookup tables corresponding to a multi-step pyrolysis mechanism are used to represent the composition of gas-phase pyrolysis products. Gas-phase and surface temperatures, mass loss, and water vapor mole fraction from the LES are shown to compare favorably with experimental measurements of a radiatively heated Douglas fir fuel sample undergoing pyrolysis and combustion beneath a cone calorimeter. Using frequency comb laser diagnostics, optical and infrared cameras, and a load cell, the experiments provide simultaneous in situ, time-resolved measurements of chemical composition, temperature, and mass loss. The present study thus combines cutting edge computational and experimental techniques with multi-step chemical pyrolysis modeling to provide a validated computational tool for the prediction of solid fuel pyrolysis and combustion relevant to wildland fires.